The importance of people and place - Emma McFadyen; Leon Benade (New Zealand Journal of Teachers' Work)
This ecofeminist-inspired research study, influenced by an ethic of care, engaged the participants in photo-elicitation and interviews. Ecofeminism originated as a theory and movement related to women and the environment (Estévez-Saá & Lorenzo-Modia, 2018), while an ethic of care stems from relational ethics that assumes human connectedness in context (Clement, 1996; Noddings, 2013). Thematic and visual narrative analysis of collected data supported the establishment of findings. The study aimed to contribute to the idea that a place-based approach can be taken to developing a holistic, meaningful and balanced local curriculum – one that privileges a ‘sense of place’ and the relationship between humans and their environments as co-habitors.